2019
DOI: 10.1158/0008-5472.can-19-0799
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA FAM225A Promotes Nasopharyngeal Carcinoma Tumorigenesis and Metastasis by Acting as ceRNA to Sponge miR-590-3p/miR-1275 and Upregulate ITGB3

Abstract: Long noncoding RNAs (lncRNA) play important roles in the tumorigenesis and progression of cancers. However, the clinical significance of lncRNAs and their regulatory mechanisms in nasopharyngeal carcinogenesis (NPC) are largely unknown. Here, based on a microarray analysis, we identified 384 dysregulated lncRNAs, of which, FAM225A was one of the most upregulated lncRNAs in NPC. FAM225A significantly associated with poor survival in NPC. N(6)-Methyladenosine (m6A) was highly enriched within FAM225A and enhanced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
249
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(255 citation statements)
references
References 55 publications
6
249
0
Order By: Relevance
“…Recently, Wu et al demonstrated that m 6 A modification upregulates lncRNA RP11 by increasing its nuclear accumulation [27]. m 6 A was suggested to be highly enriched on lncRNA FAM225A and can increase its RNA stability [26]. Herein, we revealed that m 6 A methylation was enriched within LINC00958 in HCC cells using both in silico data and m 6 A RIP experiment.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recently, Wu et al demonstrated that m 6 A modification upregulates lncRNA RP11 by increasing its nuclear accumulation [27]. m 6 A was suggested to be highly enriched on lncRNA FAM225A and can increase its RNA stability [26]. Herein, we revealed that m 6 A methylation was enriched within LINC00958 in HCC cells using both in silico data and m 6 A RIP experiment.…”
Section: Discussionmentioning
confidence: 69%
“…Recent advancements in tumor epigenetic regulation have shed light on the involvement of m 6 A modification in lncRNA [26,27]. We then wondered whether m 6 A was associated with LINC00958 upregulation in HCC.…”
Section: A Modification Is Associated With Linc00958 Upregulationmentioning
confidence: 99%
“…Studies have shown that one-third of the human genome can be regulated by miRNAs [55], which play an important regulatory role in cancers and metabolic diseases. Most miRNAs in the ceRNA network have been found to be closely related Journal of Diabetes Research to cancers [56][57][58][59]. In addition, Rohm et al [60] found that the expression of hsa-let-7d-5p was increased in the experimental group compared with the undifferentiated control group during adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, abnormal m 6 A modification contributes to the dysregulation of lncRNAs in human cancers. For example, m 6 A was highly enriched within lncRNA FAM225A and enhanced its RNA stability, resulting in nasopharyngeal carcinogenesis and metastasis [11]. m 6 A methylation was involved in the upregulation of lncRNA RP11 by increasing its nuclear accumulation in colorectal cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%